PENGARUH KEPUASAN KERJA DAN MOTIVASI TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA PEGAWAI RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PEKANBARU - Syafitri, Nur; Marnis, Marnis (Jurnal Tepak Manajemen Bisnis, 2017)
This research was conducted at the General Hospital Arifin AchmadPekanbaru. The purpose was to determine and analyze the effect of job satisfaction andwork motivation on organizational commitment, and then to determine and analyze theeffect of job satisfaction and work motivation on employee performance and to determinethe influence of organizational commitment to employee performance, and to investigateand analyze the influence job satisfaction and work motivation on employee performancethrough organizational commitment to employee outpatient at Arifin Achmad Pekanbaru.Asfor the type of data used in this research using primary and secondary data. With a totalpopulation of 149 employees and a total sample of 109 employees. Sampling using simplerandom sampling method. While analyzing the data, the authors use Path Analysis (PathAnalysis) with the help of the SPSS version 17.0.Based on the analysis of test results Line(Path Analysis) is known that job satisfaction and motivation striving to variable employeeperformance. While the indirect effect through organizational commitment. This showsthat the variable of organizational commitment capable of mediating variables jobsatisfaction and work motivation on employee performance. Therefore, to improveperformance still needed an increase in job satisfaction as attention to salaries,allowances, promotions, responsibility, achievement and their attitude of feelingchallenged, while motivation by taking into account the interests and talents of employees,the tranquility of employee attitudes toward, interaction with colleagues, interaction withsuperiors, environmental conditions, working time arrangements and working equipmentand can implement organizational commitment so that employee performance willincreased.